Reflux Control After Barrett's Esophagus Ablation. Issue 1 (March 2021) - Mittal, Sumeet K.; Baboli, Komeil Mirzaei; Bremner, Ross M.
Esophageal adenocarcinoma (EAC) is difficult to treat and carries a poor prognosis. Barrett's esophagus, which develops from long-standing gastroesophageal reflux disease is the only known precursor to EAC. Endoscopic eradication therapy is a major advancement in the treatment of dysplastic Barrett's esophagus and early EAC; however, failure to eradicate disease and a high rate of recurrence with risk of progression currently remain unacceptably high with the use of acid suppressive medication for reflux. Herein, we describe the physiology of gastroesophageal reflux and review the current literature on endoscopic eradication therapy for Barret's esophagus. We summarize that antireflux surgery for reflux control as an adjunct to endoscopic eradication therapy may decrease the need for multiple endoscopic sessions (to achieve eradication), decrease the risk for recurrence/progression, and potentially decrease the need for surveillance.